The influential role of financial reporting regulations on the disclosure levels of Islamic Banks in selected jurisdictions - Hazaa, Hani HazaaAbdulbari; Othman, Anwar Hasan Abdullah; Syed Jaafar Alhabshi, Syed Musa; Alsuwaigh, Mugbel Abdulltef (Mattingley Publishing Co., Inc., 2020)
The Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) was established in 1990 to develop different standards to guide the Islamic financial institutions around the world. Although these standards are mandatorily adopted by six countries, the level of harmonization varies from one country to another. The financial reporting regulations were found to be significantly responsible for the variation in the disclosure levels across the countries. This study helps the regulatory authorities in the selected countries to understand how their financial reporting regulations affect the harmonization process of the AAOIFI accounting standards. This is a pioneer study that investigates theoretically and empirically the influential role of the regulations on the disclosure levels across countries.